Omega-3 fatty acids in nutrition and supplementation - Hronek, Miloslav; Kovařík, Miroslav (Ceska a Slovenska farmacie, 2024)
Omega-3 fatty acids in nutrition and supplementation Omega-3 fatty acids (n-3 PUFAs) have gained significant attention in the field of nutrition and health due to their many positive effects. This article provides a review of n-3 PUFAs, including their definition, classification, structural and functional characteristics, as well as their importance in nutrition and supplementation. In addition, it describes nutritional sources, discusses maximum doses, and describes recommended daily doses.
Keywords: Dietary Supplements; EPA; omega-3 fatty acids; Fatty Acids, Omega-3; omega-3 mastné kyseliny; lidé; ALA; potravní doplňky; DHA.; Humans